Seed Bio-Priming to Enhance Seed Germination and Seed Vigor of Rice Using Rhizobacteria from The Northern Coast of Pemalang, Central Java, Indonesia - Purwanto, Purwanto; Oktaviani, Eka; Leana, Ni Wayan Anik (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2022)
The growth and yield of plants are strongly influenced by the early growth ability of the plants. Similar germination and good seed vigor will greatly support plant growth and increase production. Increasing the germination and vigor of seeds can be done through biopriming. The application of biopriming using rhizobacteria is developing environmentally friendly agricultural technology. This study aimed to determine the effect of inoculation of rhizobacteria from the north coast of Pemalang on rice plants' germination and vigor index. The study was arranged in a Randomized Block Design, consisting of 10 treatments with three replications. Ten rhizobacteria isolates were isolated from the North Coast of Pemalang, Central Java, consisting of Ju1, Jn3, Jn1, J, J12, J5, Kn1, A3, Jn, and K3. The biopriming with rhizobacteria isolated from the rice rhizosphere of the Northern Coast of Pemalang increased the seed germination rate, seed vigor index, and early vegetative growth of rice seedlings. Inoculation with isolate J12 produced the highest vigor index of 8280.01. The results of this study imply that the application of rhizobacteria from saline soil has the potential to increase the vigor of rice seedlings to impact better seedling growth in saline conditions.